2013
DOI: 10.14427/jipai.2013.3.80
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages as probiotic tools to regulate microbiocenosis and decontaminate food products, animals and plants with microorganisms

Abstract: Московский научно исследовательский институт эпидемиологии и микробиологии им. Г.Н. Габричевского 1 , Москва Государственный научный центр прикладной микробиологии и биотехнологии 2 , п. Оболенск Серпуховского района Московской области Ульяновская государственная сельскохозяйственная академия 3 , Ульяновск Первый Московский государственный медицинский университет им. И.М. Сеченова 4 , Москва Астраханская государственная медицинская академия 5 , Астрахань Bacteriophages as probiotic tools to regulate microbioce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Lytic phages, which have been reassessed for their ability to prevent and treat bacterial infections, are currently receiving increased attention. The potential of phage therapy to reduce the distribution of E. coli infection and improve the antimicrobial effectiveness of phages for elimination of E. coli pathogens in vivo in humans and animals has recently been discussed in several reports. At the same time, there are still some disadvantages delaying the broad application of phages in clinical practice. The development of bacterial resistance to phages is among the most important.…”
Section: Introductionmentioning
confidence: 99%
“…Lytic phages, which have been reassessed for their ability to prevent and treat bacterial infections, are currently receiving increased attention. The potential of phage therapy to reduce the distribution of E. coli infection and improve the antimicrobial effectiveness of phages for elimination of E. coli pathogens in vivo in humans and animals has recently been discussed in several reports. At the same time, there are still some disadvantages delaying the broad application of phages in clinical practice. The development of bacterial resistance to phages is among the most important.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages have seen a rise in use as biocontrol agents in agriculture, bioprocessing, and healthcare. 18,19 Bacteriophages are regarded as safe for animals, humans, and plants, further promoting their use in the previously mentioned industries. [20][21][22] Chibani-Chennoufi et al 23 reported that mice exposed to an oral four-phage cocktail did not experience a decline of their commensal E. coli biota.…”
Section: Bacteriophage Safety In Agricultural Products and Humansmentioning
confidence: 99%